Termites: Evolution, Sociality, Symbioses, Ecology 2000
DOI: 10.1007/978-94-017-3223-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Termites and Soil Properties

Abstract: Abstract:This chapter reviews the advances made in our knowledge of the effects of termites on the physical, chemical and biological properties of soils. Emphasis has been placed on more recent contributions, particularly those that explore new concepts in the ecology of termites and soils. There are sections dealing with the effects of termite activity on soil profile development, soil physical properties, soil chemical properties, soil microbiology and plant growth. The physical effects of termites on soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(185 citation statements)
references
References 68 publications
5
176
0
4
Order By: Relevance
“…manure, woody debris, etc.) to encourage termite activity (Nyamapfene, 1986;Logan, 1992;Batalha et al, 1995;Wood, 1996;Black & Okawol, 1997;Brouwer & Bouma, 1997;Holt & Lepage, 2000). In Australian wheat fields, Evans et al (2011) reported a 70% reduction in mineral N concentrations in soil from which termites and ants had been excluded compared with control plots.…”
Section: Implications For Productivitymentioning
confidence: 99%
“…manure, woody debris, etc.) to encourage termite activity (Nyamapfene, 1986;Logan, 1992;Batalha et al, 1995;Wood, 1996;Black & Okawol, 1997;Brouwer & Bouma, 1997;Holt & Lepage, 2000). In Australian wheat fields, Evans et al (2011) reported a 70% reduction in mineral N concentrations in soil from which termites and ants had been excluded compared with control plots.…”
Section: Implications For Productivitymentioning
confidence: 99%
“…Micas from vermiculite by weathering, releases K + and replaces other exchangeable cations mainly Ca 2+ and Mg 2+ [9,13]. Following this reason, it could be speculated that clay minerals rich in K + would be modified during the construction of termite moulds because of K + extraction by a biological metabolism of soil-feeding termites by which free charges would be neutralized with cations from organic matter such as A1 3+ .…”
Section: Modification Of Clay By Termitesmentioning
confidence: 99%
“…Since oxic horizons are generally low in silt, the contribution of this particle size fraction to exchange reaction is negligible, moreover, the small quantities of micas which might be present do not participate significantly in the possible exchange or fixation of NH 4 + by K + ions [9]. The finest soil particles are dominantly composed of Kaolinite, goethite and various amounts of other Iron and Aluminium oxides.…”
Section: Physio-chemical Propertiesmentioning
confidence: 99%
“…Termites play an important role in the transformation processes of organic compounds in savannahs and tropical forest ecosystems (e.g., Lee and Wood 1971;Bignell and Eggleton 2000;Holt and Lepage 2000;López-Hernández 2001). Data on the P content of termite mounds in relation to adjacent soils are sometimes contradictory.…”
Section: Phosphorus Contents In Termite Moundsmentioning
confidence: 99%